The Relationship between the Cultural Orientation of Physical Contact with the Level of Compliance in Avoiding Covid-19: A Case Study on Elderly of GMIT Paulus Church in Kupang City, Indonesia - LILIWERI, Aloysius; ANDUNG, Petrus Ana (Advances in Social Sciences Research Journal, 2022)
This study aims to analyze the relationship between the cultural orientation of physical contact with the level of compliance in avoiding Covid-19. This research uses a quantitative approach. The data analysis technique in this study used the Spearman rank correlation test. The results showed that there was no significant relationship between the cultural value orientation of the community's physical contact as indicated by the culture of handshakes, kissing noses, hugging each other, group habits in conversation, and speaking loudly at every meeting with the level of compliance in avoiding Covid-19. It can be concluded that the Covid-19 pandemic afflicts people with relatively the same socio-cultural background, namely the "contact culture" which (before the Covid-19 pandemic) maintained the habit of communicating face-to-face with each other. by touching each other's bodies, such as shaking hands tightly, kissing, hugging, and emotionally displaying conversations out loud. However, during the Covid-19 pandemic, the community, especially elderly as vulnerable groups, reduced close physical contact cultural activities and chose to obey the Government's appeal regarding the Health protocol to prevent Covid-19 transmission.